Evaluation of Dexamethasone as an Antiemetic in Laparoscopic Cholecystectomy - Jawad Zaheer (Journal of Rawalpindi Medical College, 2010)
Background: To determine whether intravenous Dexamethasone (8mg), during anaesthesia, would decrease early postoperative nausea and vomiting (PONV) after laparoscopic cholecystectomy (LC). Methods: In this double- blind, randomized controlled trial, hundred patients who underwent laparoscopic cholecystectomy were divided in two groups. In Group-A, 50 patients, who received Inj. Dexamethasone 8 mg were compared with Group B, a control group of fifty patients who had laparoscopic cholecystectomy but did not receive Inj. Dexamethasone. Results: Group A showed low frequency of PONV when compared to Group B(nausea 6 vs. 27 and vomiting 3 vs. 13 , with p value of < 0.001 and < 0.006 respectively. Conclusion: Inj.Dexamethasone given during anaesthesia effectively controls postoperative nausea and vomiting.